Major cardiac defects in cattle in southern Brazil: retrospective study of necropsies over 20 years (2000-2019) - Wronski,Júlia Gabriela (2021)
ABSTRACT: Cardiac malformations are reported to be relatively rare in bovine species, with ventricular septal defects being the most common abnormality observed predominantly in young calves. This report aims to describe the cardiac malformations observed in bovids and review the literature related to those malformations in this species. The necropsy reports of 1,783 bovids were reviewed, and 0.4% were diagnosed with a cardiac congenital defect. The most common cardiac congenital malformation detected in this study was ventricular septal defect, observed alone or associated with other anomalies (in one case, as part of tetralogy of Fallot); followed by atrial septal defect, also alone or with other cardiac malformations. Secondary findings in the lungs and liver were observed in 75% of all cases. Histologic cardiac lesions were identified in 25% of all cases, characterized mainly by fibrosis. Other congenital malformations in different organs were observed in 25% of the cases. Considering the importance of cardiac congenital malformations observed in this study, these conditions should be considered as a differential diagnosis for calves who died with no specific clinical signs. Furthermore, macroscopic evaluation is crucial for the diagnosis of cardiac congenital malformations.